Organizational Strategies for Enhancing Employee Performance - Ihsan, Muh. Nurul; Raharjo, Kusdi; Noerman, Teuku (Jurnal Mamangan, 2023)
This study aims to examine the effects of leadership style, organizational culture, and work environment on job satisfaction, as well as the mediating role of job satisfaction in influencing employee performance, using the Stimulus-Organism-Response (S-O-R) framework and the Theory of PlaNned Behavior (TPB). This quantitative research employed an explanatory approach with a surveymethod involving 148 non-academic staff from a public vocational institution in Indonesia. Data were collected using structured questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS software. The results show that organizational culture and work environment have a positive and significant effect on job satisfaction, while leadership style has a positive but insignificant effect. Furthermore, leadership style and work environment do not significantly affect employee performance through job satisfaction. However, organizational culture has a significant indirect effect on employee performance through job satisfaction, indicating its mediating role. These findings highlight that creating a strong organizational culture and a supportive work environment is crucial for enhancing job satisfaction, which in turn contributes to improved employee performance. This study offers practical insights for public educational institutions in developing countries by emphasizing the importance of internal organizational factors in shaping employee behavior. The integration of TPB within the S-O-R framework also provides a novel theoretical contribution by illustrating how individual attitudes and perceptions, shaped by organizational stimuli, lead to specific behavioral outcomes in the workplace context.